Кремль 2222. Тушино: [фантастический роман] / Олег Бондарев - Бондарев Олег Игоревич (Кремль, 2016)
Экземпляры: ЦБ/16 (20171024) / Инвентарный номер: 54802 / Цена: 210.00 / Сис.шифр: Р2 / Авт.знак: Б 81 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6